2017
DOI: 10.1055/s-0037-1615259
|View full text |Cite
|
Sign up to set email alerts
|

Gorham-Stout Disease Management during Pregnancy

Abstract: Gorham-Stout Disease (GSD) is a rare lymphatic disorder affecting children or young adults with no predilection of sex. It is generally associated with vanishing bone osteolytic lesions, thoracic and abdominal involvement, and diffuse pulmonary lymphangiomatosis. Chylous effusions and chylothorax, consequent to the abnormal proliferation of lymphatic vessels, may induce respiratory failure with a high mortality risk. Extrapulmonary alterations may include chylous ascites, lymphopenia, and destructing bone dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to evaluate the number and size of focal splenic lesions associated with LAs. Similar to the findings of the present study, patients with GLA [ 8 ] presented with relatively larger focal splenic lesions, whereas patients with KLA [ 7 , 9 ] or GSD [ 10 ] presented with relatively smaller focal splenic lesions on CT or MRI images, as reported in several case reports.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…To the best of our knowledge, this is the first study to evaluate the number and size of focal splenic lesions associated with LAs. Similar to the findings of the present study, patients with GLA [ 8 ] presented with relatively larger focal splenic lesions, whereas patients with KLA [ 7 , 9 ] or GSD [ 10 ] presented with relatively smaller focal splenic lesions on CT or MRI images, as reported in several case reports.…”
Section: Discussionsupporting
confidence: 91%
“…[ 6 ] Several case reports have reported multiple splenic cysts or nodules in patients with GLA, [ 8 ] KLA, [ 7 , 9 ] or GSD. [ 10 ] However, the number and size of the focal splenic lesions were mainly not revealed in these articles. In addition, no study has been reported the histopathological findings of the focal splenic lesions.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations